Argumentasi Rasional Eksistensi Tuhan - Pamungkas, Mohamad Singgih (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to examine and reiterate the arguments used by Islamic scholars regarding the existence of God, by incorporating contemporary evidence supporting the validity of these arguments. Simultaneously, it aims to refute the atheist's assumption that the existence of God is impossible to scientifically prove. This study employs qualitative, descriptive, and analytical methods, along with a philosophical approach to the arguments presented in revelation and those used by Islamic scholars regarding the existence of God. The research is categorized as library research, drawing from classical and contemporary books, relevant scientific journals, or articles related to the study. Islamic scholars, based on the Quran and Sunnah, have put forth various rational arguments for the existence of God. However, in the modern era, atheistic and agnostic groups are increasing, and their movements are extensive and structured in advocating their ideologies. Hence, there is a need to reexamine the arguments of the scholars, presenting them more explicitly with updates and additional contemporary facts, both from scientific perspectives and the testimonies of atheists or agnostics who affirm the existence of God. The results of this research indicate that the existence of God is a truth easily provable through reason and logic that is inherently certain.